Differential fault analysis on PRINTcipher. Issue 1 (1st March 2013) - Bagheri, Nasour; Ebrahimpour, Reza; Ghaedi, Navid
Abstract : The new block cipher PRINTcipher was introduced in CHES 2010 as a lightweight block cipher for 'integrated circuit' or IC‐'printing' technology. The key of PRINTcipher consist of two sub‐key components where the first sub‐key is 'XORed' to the state in each round, whereas the second sub‐key is used to generate the key‐dependent permutations. In this study, the authors describe a new differential fault analysis on the lightweight block cipher PRINTcipher . The authors present two different fault models for obtaining each sub‐key. The first fault model is used to obtain the second sub‐key, which induces a fault on the key‐dependent permutation layer so, on average, key search space is reduced from 2 32 to 2 14, given 36 faulty cipher texts. To obtain the first sub‐key, the authors induce a fault on an intermediate results then they obtain, on average, 42 bits of the first sub‐key with less than 24 faulty cipher texts. In total, on average, they reduce key search space of PRINTcipher from 2 80 to 2 20, given 60 faulty cipher texts. They also simulated their attack on a 1.8 GHz Celeron PC.